The Vitalized School - Pearson, Francis B. (Francis Bail), 1853-1938 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Vitalized School" by Francis B. Pearson is an educational treatise written in the early 20th century. This work explores the philosophy and practice of education, emphasizing the integral connection between school processes and the broader life experiences of students. Pearson advocates for a vibrant educational approach where teachers inspire children to see learning not as rote memorization but as a dynamic part of living fully. The opening of the book highlights the distinction between merely being a school teacher and effectively teaching school as an act of engaging with life. Pearson argues that true teaching involves interpreting life through educational practices, suggesting that school should be a place where students learn to embrace and understand the complexities and joys of existence. He introduces the notion that if a child's education does not enhance their life experience, then it falls short of its purpose. The author's optimistic tone invites educators to view their role as pivotal in opening the gates of life for their pupils, making learning a more enriching and fulfilling endeavor. (This is an automatically generated summary.)
Release date is 2006-01-23
E-text prepared by Barbara Tozier, Bill Tozier, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net/)
E-text prepared by Barbara Tozier, Bill Tozier, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Teaching